Analysis of Coretax System Implementation at the Abdul Rachman Tax Accountant and Consultant Services Office: Technology Acceptance Model Approach - Wayra, Hariko; Dwi Fionasari (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2025)
Based on the Decree of the Minister of Finance Number KMK-885/KMK.03/2016 on the Establishment of the Tax Reform Team (Reform Team) tasked with reforming the tax system in Indonesia, the coretax system was created. Coretax or Coretax Administration System, is a technology-based system that modernizes the management of tax administration through the application of more sophisticated information technology. The research method used is a qualitative method conducted at the Abdul Rachman Tax Accountant and Consultant Services Office. Data will be obtained by conducting direct interviews with the leadership and 2 staff at KJA and KKP Abdul Rachman regarding the coretax system that has been operated with the triangulation analysis method. The results of the study show that the implementation process of the Coretax system is carried out in stages through simulation activities, training, workshops, and internal adaptation. However, substantive challenges were also found, such as system instability, failures in the creation of billing codes, data insynchronization between Coretax and Webinvoice, as well as system features that have not worked optimally, such as errors when editing tax invoices that have been uploaded. These technical issues have a direct impact on operational activities, lead to delays in client reporting, and in some cases pose a risk of late sanctions. This study uses TAM (Technology Acceptance Model) as an analysis tool by grouping the interview findings into two main constructs, namely perceived usefulness and perceived ease of use. The two constructs of TAM ease of use and usefulness are not only the theme of the results, but also an analytical tool to answer the formulation of this research problem, namely, low ease of use due to technical constraints to early adoption barriers, high usefulness is the main motivation for use even though there are technical obstacles.